Study of hypovitaminosis D as a cause of chronic widespread pain in patients presenting to rheumatology clinic - Vaidya, Binit; Nakarmi, Shweta; Chaudhary, Arvind; Batajoo, Poojan; Rajbhandari, Nija (Journal of Advances in Internal Medicine, 2014)
Background and aims: Hypovitaminosis D is common in south-east Asian countries. Deficient vitamin-D level is likely to be associated with chronic muscular pains. We do not have data from our country regarding the magnitude of this problem. Methods: A prospective open labeled study at rheumatology opd from December 2009 to December 2012. Patients with chronic widespread pain and bone pains of >3 months duration were included in the study. Hypothyroidism, chronic renal failure and other rheumatological diagnosis except fibromyalgia were excluded. Visual analogue score (VAS) for pain and serum Vitamin-D levels were measured. Patients with low Vitamin-D were given oral Vitamin-D 60,000IU for 6 months. Response to therapy was evaluated using improvement in VAS. Results: Among 1680 patients, 66?2% were females. Hypovitaminosis-D was seen in 1388(82?6%), of which 27?5% had severe deficiency with Vitamin D levels <10ng/ml. Fibromyalgia overlap present in 25?7%. Mean initial VAS score was 8?7, 8?2 and 7?4 for patients in severe deficiency, mild deficiency and insufficiency group respectively. At 6 months follow-up, the VAS scores were 0, 2?1 and 3?6 respectively. After 6 months of treatment, no improvement was seen in 196 patients (11?6%) and all non-responders had fibromyalgia overlap. Vitamin- D level was checked again in non-responders and repeat vitamin-D levels were still low in 10 of them. Conclusions: Hypovitaminosis-D can be a significant cause of Chronic widespread pain in the general population and seems to aggravate the pain of fibromyalgia. Improvement was rapid and better in severe cases. DOI: http://dx.doi.org/10.3126/jaim.v3i1.10694 Journal of Advances in Internal Medicine 2014;03(01):1-4